Drivers of food insecurity amongst the Batwa in Uganda - Ainembabazi, Triphine (Makerere University, 2023)
Crop production is important in fostering food security. This is particularly true in Uganda, where the majority (80%) of the population rely on agriculture for sustenance. Although agriculture is important, about 30% of the country’s population is still food insecure due to climate variations, reduced soil fertility and limited livelihood diversification, among other factors. The Batwa of southwestern Uganda are an impoverished, marginalized indigenous group that are sternly food insecure. They were evicted from their traditional homeland, the Bwindi impenetrable forest, about 30 years ago to pave way for the conservation of endangered mountain gorillas. They Batwa were forced to adapt to agricultural livelihoods amidst many challenges and they have since been food insecure. Factors that influence their food insecurity have not been adequately explored. This study, therefore, examines the factors that drive food insecurity among 10 Batwa communities in Kanungu, southwestern Uganda. Five variables—land, labor, agro-inputs, rainfall and temperature—were assessed. Multilinear regression analysis was done in R studio to determine the most predictor variables and bivariate correlations were done to establish causality. The findings revealed that land and rainfall were the driving factors of food production. There was a relationship between food production and food security. While it is true that the Batwa are food insecure, some communities are worse off compared to others. Some communities still rely on handouts and ecotourism through dancing and selling crafts to tourists, which is not sustainable, making them vulnerable to food insecurity. There is a need to reinforce food production, especially with the increasing population.